Validity of a Physics E-Module Based on Creative Problem Solving Model Integrated With Renewable Energy - Widya; Fajrul Wahdi Ginting; Muhammad Iqbal; Riza Andriani (Jurnal Penelitian Pendidikan IPA, 2023)
E-modules are one of the teaching materials that can support the goals of an independent curriculum because with e-modules students can learn easily, can be accessed anywhere and at any time. The CPS model can train students to be skilled and creative in solving problems. One of the characteristics that needs to be integrated in teaching materials is energy saving. The aim of the research is to produce e-modules that meet the criteria of being feasible, practical and effective in improving student learning outcomes. This e-module was developed through research and development using the EDR (Educational Design Research) model with the following stages: analysis and exploration, design and construction, and evaluation and reflection. The Physics E-Module was developed for Work and Energy material which was developed based on Creative Problem Solving steps. Then this e-module also contains information about renewable energy and several energy saving invitations to students. The physics e-module that was developed met the very valid criteria, with detailed scores: 87.5 for the content suitability category, 87.5 for the e-module presentation category, 95.45 for the graphics category, and 91.67 for the language category. Thus, the physics e-module received a very valid assessment for all validation categories.